Bonded by battle : the powerful friendships of military dogs and soldiers : from the Civil War to Operation Iraqi Freedom - Pimm, Nancy Roe (Quindaro Press, 2017)
"A history from the Civil War onward of the partnership between military dogs and their human companions. Describes the evolving relationship as the dogs' skills are discovered and exploited by their handlers, and the U.S. military's changing policy toward the dogs."--